A case report of mycotic pseudoaneurysm in childhood: an unusual complication of coarctation of the aorta. Issue 1 (4th March 2019) - Ratsimandresy, Miarisoa; Hadeed, Khaled; Acar, Philippe; Cuttone, Fabio
Abstract: Background: We report on an unusual case of a 3 year-old girl with coarctation of the aorta complicated by mycotic pseudoaneurysm and infected with Streptococcus pneumoniae. Case summary: The only symptoms and signs were fever and weak femoral pulses. The echocardiography confirmed a localised isthmic's coarctation. In order to complete the evaluation, a CT scan was performed. This proved crucial in terms of the diagnosis and decision to perform emergency surgery. The diagnosis was confirmed surgically. An aortic rupture was contained by the parietal pleura. Bacteriological analysis of surgical specimens revealed bacterial DNA that tested positive for Streptococcus pneumoniae . The post-operative course was free from any cardiovascular or neurological complications after six weeks of antibiotic therapy. Discussion: Surgical repair of coarctation of the aorta is frequently performed in children. However, complicated forms are less common with a potentially fatal outcome. Indeed, there are no recommendations concerning the management and surgical timing of mycotic pseudoaneurysm. These rare complications should be kept in mind. Although short- and medium-term follow-up of these children is good, caution should be exercised with long-term follow-up because of complications in childhood and adulthood.